Determination of the useful frequency for the calculation of the attenuation coefficient and phase velocity in a viscoelastic Hopkinson Pressure bar - Theodorakopoulos, I.D. (Прикладная механика, 2015)
The propagation coefficient associated with the wave dispersion and attenuation in viscoelastic bars is calculated experimentally. The phase velocity and the attenuation coefficient in relation to the frequency are obtained from a series of impact tests on a PMMA Hopkinson pressure bar using ball bearing projectiles of different diameters. A wave dispersion correction technique is applied using the Fast Fourier Transforms of the longitudinal strains associated with the incident and reflected waves.